A Genetic Algorithm for Two-Dimensional Bin Packing Problem - Lee, Lai Soon (Institute for Mathematical Research, 2008)
This paper considers a non-oriented twodimensional bin packing problem, where a set of small rectangles, which may be rotated by 90°, has to be allocated to one or more identical bins. A genetic algorithm (GA) hybridised with a heuristic placement routine is proposed to solve the problem. The algorithm employs an innovative crossover operator that considers a number of different children from each pair of parents. Comprehensive results are presented, and the algorithm is shown to be competitive when compared with other metaheuristic algorithms.